Engineering solid-state photoreactivity within silver(I) organosulfonate complexes containing an ester-functionalized reactant molecule. Issue 11 (28th October 2022) - Powell, Conrad J.; Ferrence, Gregory M.; Bosch, Eric; Groeneman, Ryan H.
Abstract: The formation, structure, and photoreactivity of a pair of silver(I) complexes based upon either trifluoromethanesulfonate [Ag(CF3 SO3 )] or p -toluenesulfonate [Ag(C7 H7 SO3 )] anions along with the ester-based reactant molecule trans- 1-(4-methylbenzoate)-2-(4-pyridyl)ethylene (1 ) are reported. In both complexes, silver(I) ions form coordinated covalent bonds to the 4-pyridyl group on the olefin containing reactant molecule and due to either argentophilic interactions or close packing of a pair of silver(I) ions ultimately places a pair of carbon-carbon bonds (C = C) on neighboring molecules of 1 in a suitable position to undergo a solid-state [2 + 2] cycloaddition reaction. In particular, the complexes [Ag(CF3 SO3 )(1 )2 ]·CH3 CN and [Ag2 (C7 H7 SO3 )2 (1 )4 ] both undergo a quantitative photoreaction to yield the head-to-head photoproduct rctt -1, 2-bis(4-methylbenzoate)-3, 4-bis(4-pyridyl)cyclobutane (2 ) upon exposure to ultraviolet light. Graphical Abstract: UF0001